Turkey’s Relations with the Middle East. Political Encounters after the Arab Spring, eds. Hüseyin Işıksal, Oğuzhan Göksel, Springer International Publishing, Cham 2018, ss. 220 - Kamil Pietrasik (Facta Simonidis)
Recenzja publikacji: Turkey’s Relations with the Middle East. Political Encounters after the Arab Spring, eds. Hüseyin Işıksal, Oğuzhan Göksel, Springer International Publishing, Cham 2018, ss. 220